PENGARUH PERASAAN BAHAGIA DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU SMA NEGERI 1 WANGI-WANGI KABUPATEN WAKATOBI SULAWESI TENGGARA - Aswati, Aswati; Abbas, Bakhtiar; Ruslan, Ruslan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine and analyze the influence of happiness and emotional intelligence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi. The sample in this study consists of all teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi, totaling 56 individuals. This research employs multiple linear regression analysis. The results of the study indicate that: (1) Happiness and emotional intelligence have a positive and significant influence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi. (2) Happiness has a positive and significant influence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi. (3) Emotional intelligence has a positive and significant influence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi.